Carbapenemase-producing Enterobacteriaceae: use of a dynamic registry of cases and contacts for outbreak management. Issue 1 (January 2016) - Clarivet, B.; Pantel, A.; Morvan, M.; Jean Pierre, H.; Parer, S.; Jumas-Bilak, E.; Lotthé, A.
Summary: Background: The emergence and spread of carbapenemase-producing Enterobacteriaceae (CPE) have become a major public health problem. Control and prevention of CPE infections hinge on isolation precautions for carriers and active screening and follow-up of contacts. Aim: To implement an open registry of cases and contacts for acute outbreak management, long-term data collection and epidemiological investigation. Methods: All cases, defined as patients (infected or colonized) with a CPE-positive culture during their hospitalization, and contacts (e.g. patients cared for by the same healthcare team as a case) were registered in an ongoing database. Hospital stays were cross-referenced for every new entry and epidemiological links (e.g. shared contacts) investigated. All cases and contacts not cleared by complete screening were registered on an active list. Findings: Between October 2012 and November 2014, we registered 30 cases and 1268 contacts, among which 24 were linked to two or three separate cases. Only 6.5% of contacts fulfilled complete screening with three rectal swabs, and 1145 contacts are still registered on the active surveillance list. Two outbreaks (12 and nine cases) occurred nine months apart. Cross-referencing of hospital stays using the registry revealed epidemiological links between seemingly unrelated cases of CPE-positive patients and suggested an environmental source of transmission, which was demonstrated thereafter. Conclusion: We implemented a simple and multi-purpose tool to manage CPE episodes and investigate epidemiological links. Efforts are necessary to improve screening of contact patients who may be occult sources of transmission. A regional registry could be helpful.